PENGARUH KOMBINASI AKUPRESUR TITIK P6 DAN AROMATERAPI LEMON TERHADAP MUAL MUNTAH PADA IBU PRIMIGRAVIDA TRIMESTER 1 - m.kes, Sumiati skm; Ripiani, Lita; Meihartati, Tuti (Jurnal Medika : Karya Ilmiah Kesehatan, 2023)
Background: Pregnancy nausea vomiting are among the most common pregnancy disorders, particularly during the first trimester. There are 90% of women who experience nausea and vomiting at some point during their pregnancy. Nausea and vomiting can have an impact on the mother's health as well as the fetus's growth and development. Acupressure point P6 and lemon aromatherapy can treat nausea and vomiting without pharmaceuticals. Purpose: To determine the combination of acupressure at the Pericardium 6 (P6) and lemon aromatherapy on nausea and vomiting in primigravida mothers in the first trimester. Method: This type of research a quasi-experimental design with a one-group pretest-posttest design. PUQE instrument observation sheet measuring instrument. Result: Nausea and vomiting before the intervention, all 15 respondents (88.2%) experienced moderate nausea and vomiting, and two respondents (11.8%) experienced severe nausea and vomiting. Following the intervention, 13 respondents (76.5%) experienced mild nausea and vomiting, four (23.5%) experienced moderate nausea and vomiting, and none experienced severe nausea and vomiting. There was an effect of a combination of Pericardium 6 (P6) point acupressure and lemon aromatherapy on nausea and vomiting in first-trimester primigravida mothers at the Obstetrics Clinic of Pertamina Hospital Balikpapan with a p-value of 0.000. Conclusion: Pericardium 6-point acupressure (P6) combined with lemon aromatherapy is effective. To aid in the reduction of nausea and vomiting in first-trimester pregnant women.